KEARIFAN LOKAL, MODAL SOSIAL DAN PEMBANGUNAN BERKELANJUTAN - Sagajoka, Estherlina; Fatima, Imaculata (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2023)
This Research aims to examine and determine the relationship between local wisdom, social capital and sustainable development. The data and information used in writing this article comes from literature studies nd literature reviews of vrious writings and documents relevant to local wisdom, social capital and sustainable development. Both offline library documents written online. The result of the study show that the relationship between local wisdom (IndigenousKnoledge) and social capital with sustainable development is that local wisdom is the knowledge of local people wwho hve lived in place for a long time, base on values developed from generation. Social capitl is wwht llows local communities to survive and develop sustainably base on local wisdom, Where community knowledge in certain Fields (Economic Activities, Social activities and environmental adaption) is beneficial for the surrounding environment whilw maintaining environmental sustainability, and has been carried out for generations. From generations to generation. Knowledge of costoms and social capital are important factors that have a significant impact on community economic growth and sustainable development. Although formal reseach on Indigenous Konwledge and social capital is still scarce and currently under development, several preliminary studies on mutual cooperation and wwork institutions are very helpful for rural communities, at leas opening wider opportunities as the main benchmark for more intensive and in-depth reseach on working practices and mechanisms as well as the sustainability of lokal wisdom and social capital in Indonesia, especially in rural areas.